The influence of increasing carbon dioxide and temperature on competitive interactions between a C3 crop, rice (Oryza sativa) and a C4 weed (Echinochloa glabrescens) - Alberto, AMP; Ziska, LH; Cervancia, CR; Manalo, PA (Commonwealth Scientific and Industrial Research Organisation, 1996)
Many of the most troublesome weeds in agricultural systems are C4 plants. As atmospheric CO2 increases it is conceivable that competitive ability of these weeds could be reduced relative to C3 crops such as rice. At the International Rice Research Institute (IRRI) in the Philippines, rice (IR72) and one of its associated C4 weeds, Echinochloa glabrescens, were grown from seeding to maturity using replacement series mixtures (100:0, 75:25, 50:50, 25:75, and 0:100, % rice:%weed) at two different CO2 concentrations (393 and 594 μL L-1) in naturally sunlit glasshouses. Since increasing CO2 may also result in elevated growth temperatures, the response of rice to each CO2 concentration was also examined at daylnight temperatures of 27/21 and 37/29C. At 27/21C, increasing the CO2 concentration resulted in a significant increase in above ground biomass (+47%) and seed yield (+55%) of rice when averaged over all mixtures. For E. glabrescens, the C4 species, no significant effect of CO2 concentration on biomass or yield was observed. When grown in mixture, the proportion of rice biomass increased significantly relative to that of the C4 weed at all mixtures at elevated CO2. Evaluation of changes in competitiveness (by calculation of plant relative yield (PRY) and replacement series diagrams) of the two species demonstrated that, at elevated CO2, the competitiveness of rice was increased relative to that of E. glabrescens. However, at the higher growth temperature (37/29C), growth and reproductive stimulation of rice by elevated CO2 was reduced compared to the lower growth temperature. This resulted in a reduction in the proportion of rice:weed biomass present in all mixtures relative to 27/21C and a greater reduction in PRY in rice relative to E. glabrescens. Data from this experiment suggest that competitiveness could be enhanced in a C3 crop (rice) relative to a C4 weed (E. glabrescens) with elevated CO2 alone, but that simultaneous increases in CO2 and temperature could still favour a C4 species.